Patients’ experience of postponement of surgery for an elective caesarean delivery - Dhulab, Jaimal Ashok (My University, 2024)
Background Surgical postponement has been shown to be an indicator of quality of care and management of the operating theatre. In South African government hospitals there are many factors that lead to postponement of surgery such as staff shortages and issues relating to infrastructure. Postponement of surgical procedures results in a misuse of valuable scarce resources. Postponement of surgery may have a significant bearing on the parturient. Patients presenting for elective caesarean delivery are known to be at high risk for developing perinatal anxiety. There is limited research into the experiences of obstetric patients that have been postponed for elective caesarean delivery. Objectives To identify, explore, and relate experiences of patients who have experienced a postponement of surgery for an elective caesarean delivery. Methods A qualitative, exploratory, descriptive and contextual design was followed using phenomenological and observational methods to describe the experience of elective caesarean section delivery patients who were postponed at Rahima Moosa Mother and Child Hospital. Semi-structured, open-ended interviews were undertaken with participants between May 2021 and August 2021. Data saturation was achieved after eight interviews and the data were analysed using inductive thematic analysis. Results A complex interlink of six themes was identified revealing poor communication, which resulted in anger and frustration, as well as fear and anxiety. Patients’ interactions with healthcare workers also brought to light experiences of guilt and disempowerment. Patients indicated that support structures and coping strategies were utilized to maintain a sense of trust and reassurance in the treatment and care that they received. Conclusion Postponement of surgery has detrimental effects on patients presenting for elective caesarean delivery. Early and effective communication may improve patients’ experience of postponement. Inter-professional communication and collaboration among doctors and nurses are key to providing quality patient care.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Anaesthesiology to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Postponement of surgery; Elective caesarean delivery; Caesarean delivery